2021
DOI: 10.1186/s12913-021-06383-7
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative exploration of priorities for quality improvement amongst Aboriginal and Torres Strait Islander primary health care services

Abstract: Background Achieving quality improvement in primary care is a challenge worldwide, with substantial gaps between best practice and actual practice. Within the context of Australia, Aboriginal and Torres Strait Primary Health Care (PHC) services have great variation across settings, structures and context. Research has highlighted how these contextual differences can critically influence the success of Quality Improvement (QI) interventions and outcomes. Less understood is the interaction betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 33 publications
1
11
0
2
Order By: Relevance
“…To facilitate cultural safety being embedded and sustained within organisations despite staff turnover, our primary recommendation is to include cultural safety measures into CQI processes. These recommendations are in line with findings in similar recent research 30,31 but provide specific actions that broaden the cultural measures for CQI and show that work within ‘turbulent waters’ has been attempted. Cultural safety actions derived from the research reported in this paper are described here as measures for CQI processes for clinical services (see Box 1).…”
Section: Discussionsupporting
confidence: 83%
“…To facilitate cultural safety being embedded and sustained within organisations despite staff turnover, our primary recommendation is to include cultural safety measures into CQI processes. These recommendations are in line with findings in similar recent research 30,31 but provide specific actions that broaden the cultural measures for CQI and show that work within ‘turbulent waters’ has been attempted. Cultural safety actions derived from the research reported in this paper are described here as measures for CQI processes for clinical services (see Box 1).…”
Section: Discussionsupporting
confidence: 83%
“…CHWs (finding 1) reduce health system barriers against primary care access (finding 2) through their role in case management. CHWs further reduce health system barriers by reassuring patients that the health system will understand them, rather than making assumptions based on untrue stereotypes [ 43 , 44 ]. Finding 3 also works to negate health system barriers (finding 2) by empowering Indigenous people to self-manage their diabetes and not rely on the health system.…”
Section: Discussionmentioning
confidence: 99%
“…McDermott et al demonstrated improvements in some health behaviours (dietician referral and blood glucose self-monitoring) in intervention group, but deterioration in others (smoking and dyslipidaemia), making it difficult to correlate Indigenous Health Workers to health behaviours in this study. A recent qualitative analysis of Aboriginal and Torres Strait Islander health services found staff and community members valued Aboriginal and Torres Strait Islander team members in delivering care [ 44 ]. Pratte et al also demonstrated an improvement in clinical and behavioural outcomes with case management being a main component of intervention [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…54 This question is difficult to answer when Indigenous status is hard to determine from the content and metadata of an article. Recently, several publications denoted Indigenous cultural identity of authors as: first name, last name (Indigenous Nation), [5][6][7] thus signalling the importance of cultural authority.…”
Section: Respecting Peoples' Cultural Authority and Expertisementioning
confidence: 99%
“…The notation of cultural provenance was variable. It appeared in the byline of both the webpage header and in the pdf, 5–7 researcher positionality, 8 acknowledgements section, 9 ethics section, 10 methods section, 11 materials and methods section, 12 the introduction and preceding the methods, 13 citation format, 5 front page of author information on preprint, 14 and was indicated with additional author information symbols (*, †, ‡, §) 15 …”
Section: Introductionmentioning
confidence: 99%